Evaluation of long-term clinical and health service outcomes following coronary artery revascularisation in Western Australia (WACARP): a population-based cohort study protocol. Issue 10 (3rd October 2014) - Gardner, C; Rankin, J M; Geelhoed, E; Nguyen, M; Newman, M; Cutlip, D; Knuiman, M W; Briffa, T G; Hobbs, M S T; Sanfilippo, F M
Abstract : Introduction: Coronary artery bypass grafting (CABG) and percutaneous coronary interventions (PCI) are procedures commonly performed on patients with significant obstructive coronary artery disease to relieve symptoms of ischaemia, improve survival or both. Although the efficacy of both procedures at the individual level has been established, the impact of advances in coronary artery revascularisation procedures (CARP) on long-term outcomes and cost-effectiveness at the population level are yet to be assessed. Our aim is to evaluate a minimum of 6-year outcomes and costs for the total population of patients who had CARP in Western Australia (WA) in 2000–2005. Methods and analysis: This retrospective population cohort study will link clinical and administrative health data for a previously defined cohort including all patients in WA who had a CARP in the period 2000–2005. The cohort consists of 19 014 patients who had 21 175 procedures (15 429 PCI and 5746 CABG). We are now collecting a minimum of 6 years follow-up of morbidity and mortality data for the cohort using the WA Data Linkage System, clinical registries and hospital records, with 12 years follow-up for cases in the year 2000. Comparison of long-term outcomes for different CARP will be reported (PCI vs CABG; bare metal stents vs drug-eluting stents vs CABG). Cost-effectiveness analysis of CARP from the perspective of the healthcare sector will be performed using individual level cost data and average costs from Australian Refined Diagnosis Related Groups. Ethics and dissemination: This study has received ethics approval from the University of Western Australia, the Western Australian Department of Health and all participating hospitals. Being a large population cohort study, approval included a waiver of informed consent. All findings will be presented at local, national and international healthcare/academic conferences and published in peer-reviewed journals.